MARKET-BASED CONSERVATION PREFERENCE IN THE FOREST CONSERVATION BUSINESS - Yudhista, Rizaldy Yudhista; Karuniasa, Mahawan; Koestoer, Raldi Hendro (Journal of Environmental Science and Sustainable Development, 2024)
Earth is on the verge of rising temperatures above 1.5˚ Celsius. Passing the limit of 1.5˚ Celsius is a significant risk in living on earth as it will increase the risks of natural disasters such as drought, flood, and storm. With forests capable of absorbing greenhouse gas (GHG) emissions, the need for forest conservation areas is increasing to keep the earth's temperature below 1.5˚ Celsius. The increase in demand is facing hurdles from its financial sustainability, as well as the stakeholder's paradigm, which is still seen as a forest from a direct economic perspective. Market-based initiatives (MBI) are a concept that incentivizes stakeholders in their efforts to preserve nature. While many debates exist, it has become a significant strategy to reduce GHG emissions in many countries. With MBI's implementation, there is expected to be a paradigm shift in forestry business stakeholders from extraction to conserving nature. This research focuses on MBI's implementation in the Indonesian forestry business market through literature and in-depth discussions with MBI's market actors and stakeholders. This research also emphasizes the utilization of preference theory to analyze the significant criteria influencing business decision-maker preference. Analytical Hierarchy Process (AHP) was used to find the most preferable MBI's on Indonesia's market, and criteria derived the preference. The findings revealed that among the criteria, there were three main criteria impacting business preference over MBIs: market potential (0.476), business goal (0.146), and business experience (0.171). Carbon trading (0.572) is deemed the most preferable MBI alternative, with an overall AHP analysis consistency ratio of 0.02. This research contributes as a basis for future research in other countries on the business preference on market-based conservation.